Pengembangan Media Animasi Berbasis Direct Instruction Dengan Menggunakan Macromedia Flash Pada Materi Relasi Dan Fungsi - Rini Marlina Masumba; Utin Desy Susiaty; Hartono Hartono (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
The research methodology used by researchers in this research is a research and development approach. The researchers in this study used a research plan that combines a three-dimensional model consisting of four different development stages: Define, Design, and Develop. The participants involved in this research were class VIII students of SMP Negeri 1 Teriak. The method used in selecting the sample used a purposive sampling technique. Purposive sampling is a sampling technique that involves deliberate selection based on certain reasons. Researchers use many data collection strategies, including indirect communication tactics and measurement techniques. The data collection methods used in this research include the use of validation sheets, questionnaires, and assessment of mathematical understanding abilities. Based on the results of the discussion in this research, it can be concluded that the level of validity of interactive video learning media in the form of animated videos on relationship and function material based on direct instruction can be classified as valid with a percentage of 85.27%, the level of practicality obtained is 90.58% with very practical and high level criteria. The effectiveness obtained was 80.76% with effective criteria.